RANCANG BANGUN SISTEM INFORMASI PENGAWASAN DATA PEMILIH (SEPEDAH) PADA BAWASLU KOTA JAKARTA TIMUR - Muhammad Tuharyadi; Thomas Budiman; Daniel Rolan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
This research was carried out with the aim of (1) to produce software in the supervision of Voter Data Analysis which is still being carried out with Microsoft Excel, (2) To produce voter data accurately using software applications in accordance with ISO 91 26 standards in terms of functionality, Security, Usebility, Efficiency and Maintanibility. Research Methods in Designing Voter Data Monitoring Information Systems (SEPEDAH) include case studies, needs analysis, system design, system programming, testing, implementation, evaluation and report writing. For application design using the unified modeling language (UML). The process of this research is made interactively, starting from case literacy to implementation and testing stages of software.